Opening the door to greater phylogeographic inference in Southeast Asia: Comparative genomic study of five codistributed rainforest bird species using target capture and historical DNA. Issue 7 (6th March 2020) - Lim, Haw Chuan; Shakya, Subir B.; Harvey, Michael G.; Moyle, Robert G.; Fleischer, Robert C.; Braun, Michael J.; Sheldon, Frederick H.
Abstract: Indochina and Sundaland are biologically diverse, interconnected regions of Southeast Asia with complex geographic histories. Few studies have examined phylogeography of bird species that span the two regions because of inadequate population sampling. To determine how geographic barriers/events and disparate dispersal potential have influenced the population structure, gene flow, and demographics of species that occupy the entire area, we studied five largely codistributed rainforest bird species: Arachnothera longirostra, Irena puella, Brachypodius atriceps, Niltava grandis, and Stachyris nigriceps . We accomplished relatively thorough sampling and data collection by sequencing ultraconserved elements (UCEs) using DNA extracted from modern and older (historical) specimens. We obtained a genome‐wide set of 753–4, 501 variable loci and 3, 919–18, 472 single nucleotide polymorphisms. The formation of major within‐species lineages occurred within a similar span of time (0.5–1.5 mya). Major patterns in population genetic structure are largely consistent with the dispersal potential and habitat requirements of the study species. A population break across the Isthmus of Kra was shared only by the two hill/submontane insectivores ( N. grandis and S. nigriceps ). Across Sundaland, there is little structure in B. atriceps, which is a eurytopic and partially frugivorous species that often utilizes forest edges. Two other eurytopic species, A. longirostra and I. puella, possess highly divergent populations in peripheral Sunda Islands (Java and/or Palawan) and India. These species probably possess intermediate dispersal abilities that allowed them to colonize new areas, and then remained largely isolated subsequently. We also observed an east–west break in Indochina that was shared by B. atriceps and S. nigriceps, species with very different habitat requirements and dispersal potential. By analyzing high‐throughput DNA data, our study provides an unprecedented comparative perspective on the process of avian population divergence across Southeast Asia, a process that is determined by geography, species characteristics, and the stochastic nature of dispersal and vicariance events. Abstract : Phylogeography of taxa occupying Southeast Asia is poorly known despite its importance as a storehouse of tropical biological diversity. We use a combination of sequence capture, high‐throughput sequencing, and historical samples to conduct a region‐wide, multispecies comparative study that unveils phylogeographic patterns with unprecedented genetic resolution.